2021
DOI: 10.3389/fimmu.2021.769775
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interaction Between Mucosal Immunity and Microbiota Drives Nose and Pharynx Homeostasis of Common Carp (Cyprinus carpio) After SVCV Infection

Abstract: The crosstalk between the immune system and microbiota drives an amazingly complex mutualistic symbiosis. In mammals, the upper respiratory tract acts as a gateway for pathogen invasion, and the dynamic interaction between microbiota and mucosal immunity on its surface can effectively prevent disease development. However, the relationship between virus-mediated mucosal immune responses and microbes in lower vertebrates remains uncharacterized. In this study, we successfully constructed an infection model by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…A previous study demonstrated that Apo A-1 has bacteriostatic activity against A. hydrophila and bactericidal activity against E. coli ( 61 ). Interestingly, apoa-1 and apoa-14 were first downregulated and then upregulated during the infection process, which was consistent with the findings of a previous study in carp infected with SVCV ( 62 ). The expression of apoa-1 and apoa-14 were upregulated in the foregut, midgut, and hindgut of common carp post the second infection.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study demonstrated that Apo A-1 has bacteriostatic activity against A. hydrophila and bactericidal activity against E. coli ( 61 ). Interestingly, apoa-1 and apoa-14 were first downregulated and then upregulated during the infection process, which was consistent with the findings of a previous study in carp infected with SVCV ( 62 ). The expression of apoa-1 and apoa-14 were upregulated in the foregut, midgut, and hindgut of common carp post the second infection.…”
Section: Discussionsupporting
confidence: 92%
“…At 1, 7, 14, 28 days post infection (dpi), the common carp were anesthetized with MS-222 for sampling as previous study [36] . For histological and pathological studies, skin, gill and gut of common carp were directly taken from control and infected fish, and then fixed immediately at 4% (v/v) neutral buffer paraformaldehyde for at least 24 h. For RNA extraction and qPCR, tissues including gill, skin and gut were collected in Trizol reagent and stored at -80 °C until use.…”
Section: And Methodsmentioning
confidence: 99%